Aerobic metabolism is maintained in animal tissues during rapid sulphide oxidation activity in the symbiont-containing clam Solemya reidi - Anderson, A E; Felbeck, H; Childress, J J (Journal of Experimental Zoology, 1990)
Solemya reidi is a gutless clam that contains intracellular, symbiotic sulfur-oxidizing chemoautotrophic bacteria in its gills. It lives in burrows in highly reducing muds rich in sulfide, a compound toxic at low levels to aerobic respiration. In these habitats there is wide variation in levels of O2 and sulfide, both of which are metabolic requirements for this symbiosis. In order to assess whether the animal tissues utilize aerobic or anaerobic ATP-generating pathways in the presence of sulfide, and to determine the sulfide concentrations that might induce a shift to anaerobiosis, clams were incubated in varying levels of sulfide and oxygen. Symbiont-free foot tissues from clams incubated in various levels of sulfide (50–500 $μ$M) were analyzed for a common substrate (aspartate) and product (succinate) of invertebrate anaerobic metabolism. The concentrations of these metabolites were compared with those found in tissues of aerobic and anaerobic controls. Aerobic metabolism was maintained in animal tissues in the presence of up to 100 $μ$M sulfide, levels at which maximum autotrophy has been previously reported; however, at higher concentrations, where inhibition of autotrophy has been reported, the onset of anaerobic pathways was evident. This use of anaerobic pathways was not due to the absence of O2, the classical definition of anaerobiosis, but rather to the inhibitory effect of sulfide on aerobic metabolism. The metabolic flexibility of this species in regard to energy metabolism is clearly advantageous living as it does at the interface between a highly oxic environment and an anoxic, highly reducing one.